Evidence and innovation in housing law and policy - Fennell, Lee Anne; Keys, Benjamin J. (Cambridge : Cambridge University Press, 2017)
No area of law and policy is more central to our well-being than housing, yet research on the topic is too often produced in disciplinary or methodological silos that fail to connect to policy on the ground. This pathbreaking book, which features leading scholars from a range of academic fields, cuts across disciplines to forge new connections in the discourse. In accessible prose filled with cutting-edge ideas, these scholars address topics ranging from the recent financial crisis to discrimination and gentrification and show how housing law and policy impacts household wealth, financial markets, urban landscapes, and local communities. Together, they harness evidence and theory to capture the'state of play' in housing, generating insights that will be relevant to academics and policymakers alike. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 15 Sep 2017).
Keywords: Housing -- Law and legislation; Housing policy